ANALISIS PENYETELAN PROTEKSI ARUS LEBIH PENYULANG CIMALAKA DI GARDU INDUK 70 kV SUMEDANG - Fajar Pranayuda; Achmad Solichan; M.Toni Prasetyo (MEDIA ELEKTRIKA, 2012)
20 kV distribution of PLN is not free from distractions short circuit. Greatest short circuit fault current occurs at 20 kV bus bar. This led to widespread outages as a result of the major security operation. The aim of this study was to identify the final interruption of short circuit current, short circuit fault current to calculate and determine the values Over Current Relay (OCR) and Ground Fault Relay (GFR). This study purposed to calculate short circuit current. The subject of research is the disturbances that occurred in Cimalaka feeders. The data required for this study were obtained from the Area Manager Distribution of Bandung. The data is analyzed to determine the magnitude of short circuit current and Over Current Relay (OCR) and Ground Fault Relay (GFR) adjustment. The results show the short circuit fault current at 0% distance from feeder is 2428,391 A and short circuit current for 3 phase is 2103,049 A short circuit fault current and the second phase of 570,406 A short circuit fault current one phase to the ground. The difference in the relay settings data from the field with the calculation results showed that the differences are not too significant, so the ability of the relays is still good. Thus, the feeder protection relays Cimalaka at 70 kV substation Sumedang still good and doesn’t need to be reset. Keywords: Over Current Relay